Performing And Creating Speeches, Demonstrations, And Collaborative Learning Experiences With Cool New Digital Tools - Susan Meyer
A student doesn't have to be a programming whiz kid to use innovative technology and tools to make a great multimedia presentation, demonstration, or collaborative learning project. Many digital programs and software are easy to use and help students find the best way to package and present their information. New social networking tools can also help students reach a larger and more targeted audience with their message. There are so many cool new Web sites, software, apps, and other digital tools designed just for creating, improving, facilitating, and showcasing multimedia presentations, demonstrations, and collaborative learning experiences, and they are discussed in great detail here. Any student can create an amazing presentation or speech. All that is required is imagination, creativity, a little help from the latest digital technology, and this superb guidebook to the readily available tools and their astounding capabilities. This text supports Common Core Standards for the reading of technical accounts and texts.